Morphological, Physiological and Biochemical Changes in the Grape Variety “Hotan Red” Caused by the Occurrence of Stress Under the Influence of Saline–Alkaline Growing Conditions - Yan Song; Ruxue Li; Long Zhou; Lili Jiang; Xiong Wang (Horticulturae)
The native Hotan Red grape germplasm from Xinjiang has strong saline–alkali tolerance. To clarify the physiological mechanisms of Hotan Red grapes in response to saline–alkali stress, Hotan Red hydroponic seedlings were used as the research material in this study and were subjected to the combined saline–alkali stress treatments of 0, 40, 80, 120 and 160 mmol·L−1. After the 15th day of stress, plant height, shoot thickness, saline–alkali injury index, photosynthetic parameters, chlorophyll fluorescence parameters, osmoregulatory substance content, oxidation products and antioxidant enzymes of Hotan Red were determined. The results showed that the growth of plant height and shoot thickness of Hotan Red was inhibited, chlorophyll content decreased and the salinity damage index increased with increasing saline–alkali stress. Saline–alkali stress resulted in a non-stomatal limitation of photosynthesis in Hotan Red, which was manifested by a decrease in net photosynthetic rate, transpiration rate and stomatal conductance, and an increase in the concentration of intercellular carbon dioxide, in which the net photosynthetic rate reached a minimum value of 3.56 μmol·m−2·s−1 under 120 mmol·L−1 saline–alkali stress; the actual photochemical efficiency of PSII in the light and maximal quantum yield of PSⅡ decreased, with minimum values of 0.16 and 0.60, respectively. Accumulation of superoxide anion, hydrogen peroxide, malondialdehyde, proline, soluble sugars and soluble proteins, and enhancement of superoxide dismutase, catalase and peroxidase activities were observed in Hotan Red under saline–alkali stress. Partial least squares path model analysis showed that photosynthesis was the main driver of saline–alkali injury in Hotan Red, followed by oxidation products and antioxidant enzymes, with osmoregulators playing an indirect role. This study revealed the physiological mechanism by which Hotan Red tolerates saline–alkali stress, providing a basis for further research into the mechanism of saline–alkali tolerance in grapes.